The century of science : the global triumph of the research university - Powell, Justin J. W.; Baker, David P.; Fernandez, Frank (Emerald Publishing Limited, 2017)
In The Century of Science, a multicultural, international team of authors examine the global rise of scholarly research in science, technology, engineering, mathematics and health fields, providing insightful historical and sociological understandings of the ways that higher education has become an institution that shapes science and society.
Keywords: Universities and colleges.; Research.; elektronické knihy; electronic books